Crystallization‐induced toughness of rubber‐modified polylactide: combined effects of biodegradable impact modifier and effective nucleating agent1. (9th April 2015) - Odent, Jérémy; Raquez, Jean‐Marie; Leclère, Philippe; Lauro, Franck; Dubois, Philippe; Domb, Abraham; Slomkowski, Stanislaw
<x xml:space="preserve">Abstract</x> The co‐addition of rubber‐like poly(ε‐caprolactone‐co‐D, l‐lactide) (P[CL‐co‐LA]) as impact modifier and N, N′‐ethylenebis(stereamide) (EBS) as nucleating agent has here been investigated to tailor both the crystallization and toughness of resulting polylactide (PLA)‐based materials. In this work, 10 wt% of P[CL‐co‐LA] copolymer and different concentrations of EBS were added into PLA by twin‐screw extrusion (in a micro‐compounder) in order to establish the mechanical performances of the resulting blends upon the nucleating agent content. Crystallization behavior and impact toughness of PLA‐based materials were both enhanced and were ascribed to a clear alteration of the matrix crystallinity, spherulitic growth rate, and crystal structure upon the nucleating agent content. As a result, toughness of PLA‐based materials was considerably enhanced up to, at least, 11 times with respect to neat PLA. Such improvement of the fracture resistance upon the extent of PLA crystallinity was related to a change in the toughening mechanism from crazing to shear‐yielding (combined with crazing) through the deformation of spherulites, promoting high energy dissipation pathways as crystallization occurs. Copyright © 2015 John Wiley & Sons, Ltd.